2016
DOI: 10.1051/0004-6361/201526161
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of galactic bars from 3.6μm S4G imaging

Abstract: Context. Stellar bars play an essential role in the secular evolution of disk galaxies because they are responsible for the redistribution of matter and angular momentum. Dynamical models predict that bars become stronger and longer in time, while their rotation speed slows down. Aims. We use the Spitzer Survey of Stellar Structure in Galaxies (S 4 G) 3.6 µm imaging to study the properties (length and strength) and fraction of bars at z = 0 over a wide range of galaxy masses (M * ≈ 10 8 −10 11 M ) and Hubble t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

32
184
2
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 135 publications
(219 citation statements)
references
References 172 publications
32
184
2
1
Order By: Relevance
“…Our halo model is chosen so that at h 2.2 r , the disk accounts for 65% of the total radial force. This corresponds to the typical value estimated for an MW mass galaxy in Díaz-García et al (2016b), obtained by combining the gravitational field calculated from the 3.6 μm images using the NIRQB code (Salo et al 1999;Laurikainen & Salo 2002), with the rotation amplitudes obtained from the HI-kinematics (Courtois et al 2009 , which correspond to the maximum disk contribution to circular velocity ∼170 km s −1 (total circular velocity ∼215 km s −1 ; see Figure 1). Our standard value for gravity softening is  = h 0.01 r , and the time step is~-10 2 time units; in physical units one time unit corresponds to ∼10 Myr.…”
Section: Simulationssupporting
confidence: 73%
“…Our halo model is chosen so that at h 2.2 r , the disk accounts for 65% of the total radial force. This corresponds to the typical value estimated for an MW mass galaxy in Díaz-García et al (2016b), obtained by combining the gravitational field calculated from the 3.6 μm images using the NIRQB code (Salo et al 1999;Laurikainen & Salo 2002), with the rotation amplitudes obtained from the HI-kinematics (Courtois et al 2009 , which correspond to the maximum disk contribution to circular velocity ∼170 km s −1 (total circular velocity ∼215 km s −1 ; see Figure 1). Our standard value for gravity softening is  = h 0.01 r , and the time step is~-10 2 time units; in physical units one time unit corresponds to ∼10 Myr.…”
Section: Simulationssupporting
confidence: 73%
“…When they calculated the bar strength from the torque maps, they found a steady growth along the Hubble sequence. The same method was employed by Díaz-García et al (2016) with a large sample of ∼600 galaxies, finding a similar result. Similarly, Seidel et al (2015) used torques to estimate the bar strength and also found this growth of the bar strength from early to intermediate type of galaxies, with a sample of 16 galaxies.…”
Section: Variation Of Bar Parameters With the Morphological Type Of Tmentioning
confidence: 53%
“…This technique was initially applied to real galaxies in Wozniak & Pierce (1991) and in Wozniak et al (1995) based on the technique described by Jedrzejewski (1987). This method has been extensively used on real galaxies (Laine et al 2002;Erwin & Sparke 2003;Sheth et al 2003;Erwin 2004Erwin , 2005 Aguerri et al 2009;Díaz-García et al 2016). A variation of this technique has also been used to determine the bar length in simulated galaxies (Athanassoula et al 1990;Villa-Vargas et al 2009Athanassoula 2014).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations